SOLOK CITY HERITAGE (SoCH) - Mellya Fitri (Jurnal Pariwisata Bunda, 2021)
This article is motivated by the tourism potential, culture and creative economy that exist in Solok City. Unfortunately, it is still running independently. There is no collaboration yet. Therefore, this article aims to collaborate potentials (tourism, culture and creative economy) with academics, government, business, community / society, and the media (pentahelix) in order to increase the community's economy, reduce unemployment, alleviate poverty and increase the number of visits to the City of Solok. Some tourist attractions at  SOLOK CITY HERITAGE (SoCH) are described  to motivate any collaborations.